Perilaku sarapan pagi kaitannya dengan status gizi dan anemia pada anak sekolah dasar - Utama, Lalu Juntra; Sembiring, Anita Ch; Sine, Juni Gressilda L (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2018)
Background : The children are a nation's investment, because they are the next generation of the nation. The quality of the nation in the future is determined by the quality of children today. Indonesia and other developing countries in general are still dominated by four major nutritional problemsObjective : This research aimed to analyze prevalence of anemia, breakfast habits, nutritional status in school children and compare two childhood education centers located in public and private school in Kupang City, East Nusa TenggaraMethods : This research used 645 were included in this cross sectional study and was done in March until May 2017. The subjects were fourth, fifth and sixth grade of elementary of public school (SD bertingkat Kelapa Lima 1, SD Inpres Bakunase) and private school (SD Asumta, SD GMIT Naioni, SDI Maulafa dan SDK Don Bosco 3). Breakfast habits data were collected by filling questionnaire; nutritional status was estimated by BMI/Age , Height/Age which weight and height of subjects were measured directly; and anemia status was estimated by hemoglobin test/hemocue. The frequency of breakfast is determined based on always breakfast and no breakfast and the sample usually consume breakfast before 7 am.Result : Compare two childhood education centre was Significant differences between public and private schools were found in nutritional status variables with height for age indicators and on breakfast habits. The prevalence of anemia in elementary school children in Kupang by 27% which is measured by blood hemoglobin levels. Contribution of great family, gender and age in students were higher with regular breakfast. The difference in the variable nutritional status with height for age indicator with a value of p = 0.034 and breakfast habits with a value of p = 0.002Conclusion : The differences in breakfast habits in public and private elementary school children are thought by the role of teachers in schools and breakfast habits can help improve nutritional status and blood hemoglobin levels